Implementation of The Clean Saturday Program in The Development of Character Care For The Environment of Students at Santa Lucia Sei Rotan Private Elementary School - Ester Justina Sinaga; Yuniarto Mujisusatyo; Wanapri Pangaribuan; Isli Iriani Indiah Pane (UNIVERSITAS PAKUAN, 2023)
The formation of a caring character for the environment can be started from the school environment by maintaining the cleanliness of the school. By getting used to students taking care of the school environment, students will care about the environment around them. The purpose of this study was toanalyze 1) the process of implementing the Clean Saturday program; and 2) the implications of the Clean Saturday program on the caring character of buildings for the environment. This research uses a qualitative approach with a case study method. The research subjects were 20 students of class VI. The research location was at the Santa Lucia Sei Rotan Private Elementary School. Data collection techniques in this study were participant observation, study documentation, and questionnaires. In this study it was found that 1) the process of implementing Clean Saturday, namely routine collaborative activities, was carried out on Saturday at 12:00 WIB cleaning the school environment with an estimated time of 15-30 minutes and accompanied by the teacher; 2) the implications of the Clean Saturday Program in the formation of students' character seen from the questionnaire filled out by respondents, namely students answered Strongly Agree (19,5 %), Agree (48 %), Disagree (23,5%), Strongly Disagree (9%).The results showed the percentage of 72.5% of students answered correctly and 27.5% of students answered incorrectly. This data shows that there is an implication of the Clean Saturday program carried out by the Santa Lusia Sei Rotan Private Elementary School for the development of environmental care characters. Therefore, the Clean Saturday program can be used as an alternative for the formation of students' environmental care characters.